Development of chronic kidney disease influenced by serum urate and body mass index based on young-to-middle-aged Japanese men: a propensity score-matched cohort study. Issue 2 (7th February 2022) - Kuma, Akihiro; Mafune, Kosuke; Uchino, Bungo; Ochiai, Yoko; Enta, Kazuhiko; Kato, Akihiko
Abstract : Objective: To investigate the association between serum uric acid (SUA) level and body mass index (BMI) on the development of chronic kidney disease (CKD) in working men aged 20–60 years. Design: Retrospective cohort study. Setting: Data from employees' annual health check-ups were collected from two companies in 2009 and 2014. Participants: A total of 16 708 working men were recruited. We excluded participants with missing essential data (N=7801), who had basal estimated glomerular filtration rate (eGFR) <60.0 mL/min/1.73 m 2 and/or proteinuria (N=698) or with the absence of follow-up data (N=2). Primary outcome: eGFR <60 mL/min/1.73 m 2 and/or proteinuria (≥1+) in 2014 (defined as incident CKD). Results: The cut-off values of SUA for incident CKD were 6.6 mg/dL in both young (20–39 years old) and middle-aged (40–60 years old) men analysed by receiver operator characteristics. ORs for incident CKD were assessed on propensity score-matched (1:1) cohorts. In young participants (N=1938), after propensity score matching, a coexistence of high-level SUA (≥6.6 mg/dL) and overweight (BMI ≥25 kg/m 2 ) was a significant risk factor of incident CKD (OR=2.18, 95% CI 1.10 to 4.31, p=0.025), but high-level SUA was not an independent risk factor without overweight status (p=0.174). In middle-aged participants (N=2944) after propensity score matching, high-level SUA was a significant risk factor of incident CKD both with or without overweight (OR=1.44, 95% CI 1.02 to 2.04, p=0.037; OR=1.32, 95% CI 1.01 to 1.73, p=0.041, respectively). Conclusion: These findings suggest that high-level SUA is strongly associated with incident CKD in overweight young adult men.